Efficient High/Low Energy Zone Solid State Device Data Storage - Arslan, Şuayb Şefik; Göker, Turguy (My University, 2016)
Methods and apparatus associated with storing data in high or low energy zones are described. Example apparatus include a data storage system (DSS) that protects a message using an erasure code (EC). A location in the DSS may have an energy efficiency rating or a latency. Example apparatus include circuits that produce EC encoded data that has a likelihood of use, that select a location to store the EC encoded data in the DSS based on the energy efficiency rating, the latency, or the likelihood of use, that store the EC encoded data in the loca tion, and that compute an order of retrieval for EC encoded data stored in the location. The order of retrieval may be based on the energy efficiency rating or the latency. The EC encoded data may also have a priority based on the number of erasures for which the EC corrects.